1999
DOI: 10.1007/s004320050325
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-associated expression of vascular endothelial growth factor and its receptors FLT-1 and KDR

Abstract: The expression patterns of vascular endothelial growth factor (VEGF) and its two receptors, flt-1 and KDR, were assessed in normal human melanocytes, transformed melanocytes expressing the simian virus 40 Tgene (SV40T), and melanoma cells derived from primary and metastatic lesions. Constitutive expression of VEGF, flt-1, and KDR mRNA and proteins was observed in the majority of primary and metastatic melanoma cell lines, and in SV40T-transformed melanocytes. VEGF expression in melanoma cell lines was further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 31 publications
4
73
3
Order By: Relevance
“…Angiogenesis and melanoma M Streit and M Detmar these studies demonstrated that VEGF expression is not as prominent in melanomas as in most epithelial cancers (Dvorak et al, 1995) and, therefore, might not represent the major angiogenic activity in these tumors, the expression of functional VEGF receptors on human melanoma cells suggests the intriguing possibility that VEGF might also exert autocrine effects on the tumor cells themselves (Gitay-Goren et al, 1993;Liu et al, 1995;Graeven et al, 1999;Lacal et al, 2000). Expression of mRNA for basic fibroblast growth factor (bFGF, FGF-2), a potent angiogenesis factor, has been detected in metastatic and primary invasive melanomas, whereas melanocytes in benign nevi did not express this factor (Reed et al, 1994) .…”
Section: Expression Of Angiogenesis Modulators By Human Melanomasmentioning
confidence: 99%
“…Angiogenesis and melanoma M Streit and M Detmar these studies demonstrated that VEGF expression is not as prominent in melanomas as in most epithelial cancers (Dvorak et al, 1995) and, therefore, might not represent the major angiogenic activity in these tumors, the expression of functional VEGF receptors on human melanoma cells suggests the intriguing possibility that VEGF might also exert autocrine effects on the tumor cells themselves (Gitay-Goren et al, 1993;Liu et al, 1995;Graeven et al, 1999;Lacal et al, 2000). Expression of mRNA for basic fibroblast growth factor (bFGF, FGF-2), a potent angiogenesis factor, has been detected in metastatic and primary invasive melanomas, whereas melanocytes in benign nevi did not express this factor (Reed et al, 1994) .…”
Section: Expression Of Angiogenesis Modulators By Human Melanomasmentioning
confidence: 99%
“…Moreover, clinical studies have shown that PlGF levels of expression in tumour cells correlate with poor prognosis in various tumours types (1,2). In human melanoma cell lines, the expression of this cytokine and of VEGFR-1 has been described, and a correlation between PlGF expression and tumour progression has been suggested (10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated the co-expression of PlGF and VEGFR-1 in a large number of human melanoma cell lines (10) and, together with other groups, suggested that the interaction of PlGF with VEGFR-1 might modulate cellular pathways important for melanoma cell proliferation, apoptosis and invasiveness (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 87%
“…Melanoma cells have been shown to secrete VEGF and angiogenesis has been demonstrated in uveal melanoma and its metastasis. 2,3 It has been speculated that inhibition of VEGF may diminish the metastatic potential by avoiding angiogenesis, providing a possible role for bevacizumab. 23 However, a large variation of tumour VEGF expression has been reported in uveal melanoma and expression of VEGF may correlate with poor prognosis.…”
Section: Animal Modelsmentioning
confidence: 99%
“…VEGF levels have been demonstrated to be elevated in choroidal melanoma. 2,3 However, the use of anti-angiogenic agents such as bevacizumab -a recombinant humanised anti-VEGF monoclonal antibody -has not been extensively investigated for the treatment of choroidal melanoma.…”
mentioning
confidence: 99%